2017
DOI: 10.1136/bmjopen-2017-018647
|View full text |Cite
|
Sign up to set email alerts
|

Sharing and reuse of individual participant data from clinical trials: principles and recommendations

Abstract: ObjectivesWe examined major issues associated with sharing of individual clinical trial data and developed a consensus document on providing access to individual participant data from clinical trials, using a broad interdisciplinary approach.Design and methodsThis was a consensus-building process among the members of a multistakeholder task force, involving a wide range of experts (researchers, patient representatives, methodologists, information technology experts, and representatives from funders, infrastruc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
188
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 139 publications
(190 citation statements)
references
References 38 publications
0
188
0
2
Order By: Relevance
“…The consensus document covers all stages of the data sharing life cycle and is highly structured, with 7 main topics, 10 principles assigned to these topics and 50 specific recommendations, making the analysis process relatively straightforward 6 . The specification of processes/subprocesses, actors and services/tools was agreed between the experts in telephone conferences and by written communication, and summarized in a table with listings.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The consensus document covers all stages of the data sharing life cycle and is highly structured, with 7 main topics, 10 principles assigned to these topics and 50 specific recommendations, making the analysis process relatively straightforward 6 . The specification of processes/subprocesses, actors and services/tools was agreed between the experts in telephone conferences and by written communication, and summarized in a table with listings.…”
Section: Methodsmentioning
confidence: 99%
“…the Institute of Medicine report in the US 1 , the Nordic Trial Alliance Working Group on Transparency and Registration for the Nordic countries 2 , the good practice principles for sharing IPD from publicly funded trials by MRC, UKCRC, CRUK and Wellcome, in the UK 3, 4 , or the guide to publishing and sharing sensitive data for Australia 5 ). Within the EU Horizon 2020 funded project CORBEL (Coordinated Research Infrastructures Building Enduring Life-science Services) and coordinated by the European Clinical Research Infrastructure Network (ECRIN), an interdisciplinary and international stakeholder taskforce reached a detailed consensus on principles and recommendations for data sharing of clinical trial data 6 . That document was taken as the starting point for the current paper.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast with data repositories established specifically for scientific research purposes (eg, UK Biobank31), which have very broad consent for data reuse,32 trials might not always have asked for a sufficiently broad consent. However, compared with routinely collected data (which have even greater consent challenges in light of the 2016 EU General Data Protection Regulation33), RCT data might prove more accessible, especially if trials begin to adopt broad consent for data reuse, as recommended 34. It is likely that researchers will need to consult their institutional review board before using RCT data for secondary analysis, but whether this satisfies ethical and legal requirements needs further examination.…”
Section: Threats To the Viability Of Rct Data Usementioning
confidence: 99%
“…Therefore, researchers who have had little incentive to share data now find that there is no choice but to do so, as more members of the research community recognize that data resulting from publicly funded clinical trials are a public good, to be made openly available with as few restrictions as possible 14. The NTRR is the mechanism that trauma researchers can now use to meet such funder and publisher requirements.…”
Section: Ntrr Enters An Emerging Data Sharing Landscapementioning
confidence: 99%
“…Researchers are concerned about the barriers to data sharing, even as the benefits are well documented and requirements for doing so come due 8. Still at issue are the resources required to prepare data for sharing, the potential for other users to misinterpret data, and the possibility that the original researchers—the ones who did all the work to design and conduct the trials—may not be able to publish as many articles using the data as they might otherwise have 14. In a recent survey of more than 7700 researchers, Springer Nature reported that among the medical sciences researchers surveyed (2683 respondents), 39% shared data neither through supplements nor repositories 8.…”
Section: Data Sharing Brings Both Benefits and Challengesmentioning
confidence: 99%